Cardiac myxomas: characteristics and outcomes in a tertiary center. (3rd October 2022) - Grazina, A; Teixeira, B; Ferreira, V; Castelo, A; Garcia Bras, P; Viegas, J M; Cardoso, I; Moura Branco, L; Galrinho, A; Timoteo, A T; Rio, P; Coelho, P; et al.
Abstract: Introduction: Cardiac myxoma (CM) is the most common primary cardiac tumour. It can manifest in a variety of clinical presentations or it can be asymptomatic and, ultimately, be detected with image techniques. The only successful treatment of these tumours is surgical excision, with low complications and recurrence rate. Objectives: This analysis aims to describe the clinical forms of presentation and echocardiographic characteristics of cardiac myxomas, establish myxoma features associated with obstructive symptons, as well as describe the postoperative outcome and long-term recurrence in a tertiary center. Methods: Between 1990 and 2021, 88 patients were diagnosed with cardiac myxoma. 84 were included in this analysis. Baseline characteristics, clinical presentation, echocardiographic findings and outcomes were noted retrospectively. A binary logistic regression analysis using SPSS statistics software, version 25.0 was performed to establish myxoma features associated with atrioventricular valves obstruction. Results: Mean age was 63±12 years old, 75% female. All CM were sporadic. The majority of the patients (52.4%, n=44) were asymptomatic, embolic events were present in 22.9% of the patients (n=19), with the most common site being central nervous system (19.0%, n=16) and constitutional symptoms in 16.7% (n=14), the most frequent fatigue (11.9%, n=10). Atrial fibrilation was present in 9.6% of the patients (n=8). The majority of the myxomas were located in the left atrium (88.1%), followed by right atrium (10.7%) and right ventricle (1.2%). Mean myxoma dimension was 36.8±17.4mm (longer axis), with heterogeneous aspect in 63.1%, presence of calcification in 11.9%, pediculated insertion in 40.5%, mobility in 70.2% and irregular borders in 52.4%. Moderate or severe ventricular inflow obstruction was present in 13.1% (n=11), 13.6% with mitral obstruction in the left atrial myxomas and 11.1% with tricuspid obstruction in the right atrial myxomas. CM longer axis 40–59mm and superior to 60mm were independently associated with obstruction (OR 5.1, 95% CI 1.4–18.4, p0.014 and OR 11.5, 95% CI 2.9–45.4, p0.001, respectively). No other morphologic features were associated with mitral or tricuspid obstruction. All but 3 patients had the myxoma surgically removed because of advanced age and comorbidities (96.4% surgical rate). There was no in-hospital or 1 year mortality in these patients. During the follow-up period, 3.6% patients had recurrence of the myxoma, with a men period of 5 years after the first surgery (one, two and twelve years), all of them re-submitted to surgical excision. Conclusion: Despite being asymptomatic in the majority of the patients and often diagnosed incidentally, cardiac myxomas are frequent source of morbidity and mortality due to embolic events, obstructive and constitutional symptoms. Surgery is the treatment of choice for cardiac myxomas and in most cases it is curative, with low complications and low recurrence rate. Funding Acknowledgement: Type of funding sources: None.